Equity Participation Contracts and Investment: Some Theoretical and Empirical Results (American Journal of Islam and Society, 1992)
Profit-sharing contzacts have recently captured the attention of academicians,bankers, and policymakers, particularly those in the Middle East. These contractsare characterized by risk sharing, an element that forces the contracting parties(especially the financier) to fund only sound projects. The theoretical analysesof such contracts have received a major boost from a variety of models, includingKhan (1986) and Haque and Mirakhor (1986), and empirical support from, forexample, Darrat (1988) and Bashir et al. (1991). The bold claim of these modelsis that if the interest payment on financial capital were to be replaced by the profit sharingarrangement, the level of investment would be enhanced instead ofweakened.A commonly used profit-sharing financial contract is known as musharakah(equity participation). This contract is a limited partnership in which theinvestor(s) and the entrepreneur pool their capital to finance a specific investmentproject. Another version of musharukah involves the investor participating inan existing enterprise by contributing capital. In both cases, the pro-ratadistribution of profit is stated in the contract and losses are shared accordingto capital contribution. The investor is eligible to participate in the project’smanagement, but may also waive this right.’A musharakah arrangement can be modeled as a two-person, two-periodpartnership game. In this setup, each player‘s utility depends on the other player’saction through a commonly observed consequence (profit), which is itself afunction of both players’ actions and an exogenous stochastic environment. Thegame is thus one of decentralized decision making in which individual optimizers ...